2021
DOI: 10.20944/preprints202103.0542.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensor Validation and Diagnostic Potential of Smartwatches in Movement Disorders

Abstract: Smartwatches provide technology-based assessments in Parkinson’s disease (PD). We present results for sensor validation and disease classification via Machine Learning (ML). A comparison setup was designed with two different series of Apple smartwatches, one Nanometrics seismometer and a high-precision shaker to measure tremor-like amplitudes and frequencies. Clinical smartwatch measurements were acquired from a prospective study including 450 participants with PD, differential diagnoses (DD) and healthy parti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…110 Wrist sensor data collected during stationary assessments at home in individuals with Huntington's disease were used to train a model to estimate the probability of chorea 111 and studies have demonstrated the utility of IMUs in smartphones and wrist devices to capture characteristics of tremor in Parkinson disease and essential tremor. 81 112 113 114 115 116 117 118 Passive data from wrist sensors have been shown to be useful for assessment of arm motor function in acute/subacute stroke, 119 120 121 122 123 prediction of 3-month poststroke disability, 124 and assessment of daily arm use months to years after stroke. 125 126 127 Wrist sensor data have also been shown to correlate with improvement in upper extremity function during stroke recovery.…”
Section: Overview Of Digital Phenotyping Research By Behavioral Categorymentioning
confidence: 99%
“…110 Wrist sensor data collected during stationary assessments at home in individuals with Huntington's disease were used to train a model to estimate the probability of chorea 111 and studies have demonstrated the utility of IMUs in smartphones and wrist devices to capture characteristics of tremor in Parkinson disease and essential tremor. 81 112 113 114 115 116 117 118 Passive data from wrist sensors have been shown to be useful for assessment of arm motor function in acute/subacute stroke, 119 120 121 122 123 prediction of 3-month poststroke disability, 124 and assessment of daily arm use months to years after stroke. 125 126 127 Wrist sensor data have also been shown to correlate with improvement in upper extremity function during stroke recovery.…”
Section: Overview Of Digital Phenotyping Research By Behavioral Categorymentioning
confidence: 99%